CRIME as the categorial concept and category - Змійова, Ірина Володимирівна; Калюжна, Алевтина Борисівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
The article focuses on a notional category CRIME. Its structure is stipulated by notional characteristics of the categorial concept CRIME that is verbalized in the English language and serves as a classifier of this category. The lexicalized notional category CRIME is structured as a radial category at superordinate and subordinate levels with members of the category being in hyper-hyponymic relations and forming subcategories and extensions structured radially on the general CENTER – PERIPHERY principle. The data obtained demonstrate the relative similarity of the category CRIME members as there is partial identity between the members which is based on a different number of semantic components. Numerous means of verbalization of the category classifier – the concept CRIME are grouped into synonymic series according to the nuances of meaning and form the basis for identifying subcategories and extensions within the notional category CRIME. Names of crimes against person and crimes against property serve as the grounds for structuring the notional category CRIME. On this basis two parts have been singled out within the superordinate category CRIME: CRIME 1 (against person) and CRIME 2 (against property) with these parts being encompassed by six subordinate categories. The categories VIOLENCE, KIDNAPPING and KILLING belong to the subordinate level and come into the superordinate category CRIME 1 (against person). The superordinate category CRIME 2 (against property) also include three subordinate categories TRESPASS, THEFT and VANDALISM. Some subcategories have a certain number of extensions. Thus, the paper provides the method of structuring a category on the basis of categorial concepts.